2004
DOI: 10.1074/jbc.m307974200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Critical Role of the Tumor Necrosis Factor α Convertase (TACE) in Ectodomain Shedding of the p75 Neurotrophin Receptor (p75NTR)

Abstract: Protein ectodomain shedding, the proteolytic release of the extracellullar domain of membrane-tethered proteins, can dramatically affect the function of cell surface receptors, growth factors, cytokines, and other proteins. In this study, we evaluated the activities involved in ectodomain shedding of p75 NTR , a neurotrophin receptor with critical roles in neuronal differentiation and survival. p75 NTR is shed in a variety of cell types, including dorsal root ganglia cells and PC12 cells. In Chinese hamster ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 77 publications
4
114
0
Order By: Relevance
“…Our preliminary data revealed an increase by 30 % of ADAM-10 mRNA expression in the cortex of 12-month-old animals that returned to the control level in aged animals (data not shown). On the other hand, the 55-kDa p75ECD fragment detected in our study was reported as a complete p75NTR ectodomain cleaved by γ-secretase in response to NGF (Weskamp et al 2004). The presence of this fragment in middle-aged animals implies that γ-secretase-dependent ectodomain shedding occurs as well, and that shedding efficiency is lost during aging.…”
Section: Discussionmentioning
confidence: 63%
“…Our preliminary data revealed an increase by 30 % of ADAM-10 mRNA expression in the cortex of 12-month-old animals that returned to the control level in aged animals (data not shown). On the other hand, the 55-kDa p75ECD fragment detected in our study was reported as a complete p75NTR ectodomain cleaved by γ-secretase in response to NGF (Weskamp et al 2004). The presence of this fragment in middle-aged animals implies that γ-secretase-dependent ectodomain shedding occurs as well, and that shedding efficiency is lost during aging.…”
Section: Discussionmentioning
confidence: 63%
“…The observed cell type-specific regulation of p75 shedding by neurotrophins might be related to the cell typespecific expression and distribution of metalloproteases; for instance those belonging to the ADAM family, and to the signal transduction system by which these metalloproteases are regulated. For example, the enzymatic activity of ADAM17, a prominent p75 sheddase (35,66,67), is regulated through phosphorylation by ERK1/2, kinases known to be activated by TrkA (68). Thus, TrkA activation may indirectly regulate ADAM17 activity.…”
Section: Discussionmentioning
confidence: 99%
“…In support, MMPs can shed the extracellular portion of the Nogo receptor (NgR) 32 and of the p75NTR, 33 molecules that are involved in inhibiting axonal growth. After experimental spinal cord injury (SCI), the MMP-2 activity that increases between 7 to 14 days after the insult is associated with the clearance of proteoglycans that retard axonal regrowth correlating with functional recovery.…”
Section: The Beneficial Functions Of the Mmps In The Cns In Developmementioning
confidence: 99%